SERODIAGNOSIS OF HAEMONCHOSIS IN SMALL RUMINANTS - A. Z. Durrani; N. Kamal; M.S.Khan (Journal of Animal and Plant Sciences, 2007)
In the present study an attempt was made to find out the incidence of haemonchosis in ovine and caprine through the DID and IHA tests. The results of the study showed higher incidence in sheep (72.5%) than goats (56%).The age wise incidence in sheep was recorded as 79.16% between 1 to 3 years of age whereas in case of goat it was 70.3% in the same age group. In sheep 16.7% animals suffered from mild form while for moderate and high forms the percentages recorded were 70.8 and 12.5. In goats only mild (33.3%) and moderate forms (66.7%) were recorded. Seasonal incidence showed that the parasitism was the highest in July/August (47.7%) while it was the least in September/October (3.1%). The sensitivity of faecal culture was recorded as 42 % while for DID and IHA it was 47 % and 56 %, respectively. The specifity of faecal culture was recorded as 89.5 % while for DID and IHA it was 94.7 % and 98.2 %.
Keywords: Haemonchosis; DID; IHA; Faecal culture